2022
DOI: 10.3390/nu14194017
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and FGF1 Synergistically Ameliorates Doxorubicin-Induced Cardiotoxicity via Activation of SIRT1-NRF2 Pathway

Abstract: Doxorubicin (DOX) has received attention due to dose-dependent cardiotoxicity through abnormal redox cycling. Native fibroblast growth factor 1 (FGF1) is known for its anti-oxidative benefits in cardiovascular diseases, but possesses a potential tumorigenic risk. Coincidentally, the anti-proliferative properties of resveratrol (RES) have attracted attention as alternatives or auxiliary therapy when combined with other chemotherapeutic drugs. Therefore, the purpose of this study is to explore the therapeutic po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…In a similar study, it was reported that Paraquat which is known as a pesticide, increases connective tissue growth factor expression and impairs lung fibroblast proliferation and viscoelasticity (Zhang et al, 2014). It has also been reported that Res has a synergistic protective effect against cardiotoxicity and hepatotoxicity in experimental studies (Lu et al, 2022;Xu et al, 2022). Thus, it is seen that the immuno-histochemical results of FGF-1 in lung sections are very similar to the literature.…”
Section: Discussionsupporting
confidence: 77%
“…In a similar study, it was reported that Paraquat which is known as a pesticide, increases connective tissue growth factor expression and impairs lung fibroblast proliferation and viscoelasticity (Zhang et al, 2014). It has also been reported that Res has a synergistic protective effect against cardiotoxicity and hepatotoxicity in experimental studies (Lu et al, 2022;Xu et al, 2022). Thus, it is seen that the immuno-histochemical results of FGF-1 in lung sections are very similar to the literature.…”
Section: Discussionsupporting
confidence: 77%
“…The speculation for this special phenomenon is that FGF1 promotes the initiation of autophagy leading to a compensatory increase in SQSTM1/p62 ( Geffken et al, 2022 ). Another speculation is that during the action of FGF1, a different pathway is activated, leading to an increase in the expression of SQSTM1/p62 and thus promoting endometrial thickening ( Feng et al, 2017 ; Lu et al, 2022 ). But the details need to be explored in subsequent studies.…”
Section: Discussionmentioning
confidence: 99%
“…Toxic chemicals and electrophiles promote the shift toward oxidative stress and trigger rapid translocation of Nrf2 into the nucleus where it binds to antioxidant response elements (AREs) of target genes including NAD(P)H dehydrogenase [quinone] 1 ( Nqo1 ), heme oxygenase 1 ( HMOX1 ) and superoxide dismutase 1, -2 ( SOD1 , -2 ) ( Figure 5 ) [ 55 ]. The targeted upregulation of gene expression of this endogenous antioxidant response results in potent antioxidant and cytoprotective activities to effectively ameliorate DOX-induced oxidative stress, which is similarly used by potent Nrf2 inducers such as resveratrol [ 60 , 61 ], sulforaphane [ 62 , 63 , 64 ] and bardoxolone-methyl [ 65 , 66 ]. Our study is the first to report decreased Keap1 protein expression following acute DOX treatment in human iPSC-CMs, which is consistent with newly synthesized Nrf2 escaping Keap1-dependent ubiquitination and rapid proteasomal degradation ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%